Preparation method and application of nano astaxanthin aggregate compound

Through the method of inducing self-assembly of carrier proteins by pH synergistic ethanol, the existing astaxanthin aggregates have poor photothermal stability, poor water solubility and low bioavailability. Nanoastaxanthin aggregate complexes with high water solubility, photostability and thermal stability have been prepared, which significantly improves its bioavailability.

CN119950751AActive Publication Date: 2025-05-09SOUTH CHINA AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202510234000.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-05-09
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing astaxanthin aggregates have shortcomings in photothermal stability, water solubility and bioavailability, resulting in limited applications in food, drugs, cosmetics and other industries.

Method used

The self-assembly of the carrier protein is induced by pH synergistic ethanol, and the ethanol is removed first and then the pH is adjusted. Astaxanthin aggregates are embedded twice to prepare nanoastaxanthin aggregate complexes.

Benefits of technology

This method makes the nanoastaxanthin aggregate complex have good water solubility, photostability and thermal stability, and has high retention rate and improved bioavailability in the digestive system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119950751A_ABST
    Figure CN119950751A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a nano astaxanthin aggregate compound, and the preparation method comprises the following steps: S1, dissolving carrier protein in water, and adjusting the pH value to 9-12 to obtain a protein aqueous solution; s2, mixing the protein aqueous solution with a saturated ethanol solution of astaxanthin to obtain a composite solution; s3, removing ethanol in the composite solution, and then adjusting the pH value to be neutral, so as to obtain the nano astaxanthin aggregate compound. According to the preparation method, self-assembly of carrier protein is induced through cooperation of pH and ethanol, and the astaxanthin aggregate is embedded twice according to a specific sequence of removing ethanol and then adjusting pH, so that the prepared nano astaxanthin aggregate compound has good water solubility and storage stability; the light stability and the heat stability are excellent, and the retention rate and the bioavailability of the astaxanthin after the digestion stage are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nano-embedding technology, and more specifically, to a preparation method of a nano-astaxanthin aggregate complex and application thereof. Background Art

[0002] Astaxanthin is a non-vitamin A derived ketone fat-soluble carotenoid, and is a natural pigment widely found in nature. At the same time, as an oxygen-containing derivative of carotenoids, its natural accumulation in marine crustaceans and specific microalgae can reach more than 85% of the total carotenoids. Due to the excellent coloring power of astaxanthin and its aggregation-induced absorption spectrum shift, crustaceans and birds rich in astaxanthin in biological tissues present different colors. In addition, astaxanthin has a variety of physiological activities, such as scavenging free radicals in the body, anti-aging, anti-tumor, prevention of cardiovascular disease, protection of the liver, anti-ultraviolet, anti-inflammatory, and improvement of athletic ability. With the continuous deepening of research, astaxanthin is becoming more and more widely used in global food, medicine, cosmetics, aquaculture and other industries.

[0003] Higher animals cannot synthesize astaxanthin by themselves and can only obtain it through food. However, due to the presence of highly unsaturated structure and conjugated double bonds, astaxanthin is easily degraded by high temperature, light and oxygen. In addition, astaxanthin is endowed with high lipophilicity. Due to its chemical structure consisting of a polyene chain connected by two terminal rings, it has poor water solubility and is easily degraded during human digestion, which leads to low bioavailability, greatly limiting its wide application.

[0004] Studies have shown that hydrophobic astaxanthin monomer molecules can aggregate in hydrated solvents to produce two significantly different aggregates. One is the card-packed H aggregate, which is composed of astaxanthin monomer molecules stacked in parallel conjugated chains "face to face", and its maximum absorption wavelength is blue-shifted from 480nm of the monomer to 380-388nm; the other is the head-to-tail J aggregate, which is composed of loose astaxanthin monomer molecules stacked in parallel, and its maximum absorption wavelength is red-shifted from 480nm of the monomer to 515-533nm, accompanied by a shoulder peak of 550-575nm. Compared with astaxanthin monomers, astaxanthin aggregates can present richer colors, so they can be used as colorants to make food look better. However, in nature, H aggregates and J aggregates will dynamically transform and are difficult to exist in a stable dispersed form in water. Like astaxanthin monomers, they are easily degraded under high temperature or light.

[0005] In existing research, astaxanthin is often encapsulated, such as preparing delivery systems such as emulsions, microcapsules, and nanocomposites. For example, a Chinese patent discloses a method for preparing a highly water-dispersible H-type or J-type aggregate astaxanthin / lactate / chitosan nano-astaxanthin aggregate complex and its application. By mixing the astaxanthin organic phase, the whey protein aqueous phase, and the chitosan aqueous phase under specific conditions, the emulsified rotary evaporation-molecular self-assembly technology is used to obtain a highly water-dispersible astaxanthin aggregate / lactate / chitosan nano-astaxanthin aggregate complex. It only focuses on the stability at room temperature and under light-proof conditions. However, during the processing of food, cosmetics and other products, astaxanthin or its complex will inevitably be exposed to light, heat (such as 60°C) and other factors and degrade. In addition, the patent does not focus on the degradation in the human digestive system.

[0006] Therefore, it is necessary to obtain astaxanthin aggregates with good light stability, good thermal stability, good water solubility, not easily degraded in the digestive system, and high bioavailability so as to make them market competitive in the food, medicine, cosmetics, aquaculture and other industries. Summary of the invention

[0007] The primary purpose of the present invention is to overcome the problems of poor light and heat stability, poor thermal stability, poor water solubility, easy degradation in the digestive system, and low bioavailability of the above-mentioned existing astaxanthin aggregates, and to provide a method for preparing a nano-astaxanthin aggregate complex. The preparation method uses pH to coordinate ethanol to induce carrier protein self-assembly, and embeds astaxanthin aggregates twice in a specific order of first removing ethanol and then adjusting pH, so that the prepared nano-astaxanthin aggregate complex not only has good water solubility and storage stability, but also has excellent light stability and thermal stability, and has a high retention rate and bioavailability of astaxanthin after the digestion stage.

[0008] A further object of the present invention is to provide a nano-astaxanthin aggregate complex.

[0009] Another object of the present invention is to provide the use of the above-mentioned nano-astaxanthin aggregate complex in the preparation of additives.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] A method for preparing a nano-astaxanthin aggregate complex comprises the following steps:

[0012] S1. The carrier protein is dissolved in water and the pH is adjusted to 9-12 to obtain a protein aqueous solution;

[0013] S2. The protein aqueous solution and the saturated ethanol solution of astaxanthin are mixed to obtain a composite solution;

[0014] S3. first removing the ethanol in the composite solution, and then adjusting the pH to neutral to obtain the nano-astaxanthin aggregate complex;

[0015] In step S2, the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution is 1:(1-9); the concentration of the carrier protein in the composite solution is 0.002-0.12 mg / mL.

[0016] The preparation method of the nano-astaxanthin aggregate complex of the present invention firstly unfolds and dissociates the carrier protein into subunits under specific pH conditions, thereby exposing a large number of hydrophobic groups inside the carrier protein and avoiding residual large-sized carrier protein particles, and then introduces a saturated ethanol solution of astaxanthin. The ethanol in the saturated ethanol solution of astaxanthin is used as a solvent to introduce astaxanthin and further unfold the carrier protein. Astaxanthin generates astaxanthin aggregates in the composite solution and binds to the hydrophobic micro-regions on the surface of the carrier protein through hydrophobic interactions. Then, the ethanol is removed to make the unfolded carrier protein fold back for the first time, and the astaxanthin aggregates are embedded for the first time; the pH is adjusted to neutral to make the carrier protein fold back for the second time, and the originally loose structure of the carrier protein becomes dense, and the astaxanthin aggregates are embedded for the second time to obtain the nano-astaxanthin aggregate complex.

[0017] The present invention uses pH to coordinate ethanol to induce carrier protein self-assembly, and embeds astaxanthin aggregates twice in a specific order of first removing ethanol and then adjusting pH, so that the prepared nano astaxanthin aggregate complex not only has good water solubility and storage stability, but also has excellent light stability and thermal stability, and high retention rate and bioavailability of astaxanthin after the digestion stage. In addition, the preparation method of the present invention has an encapsulation rate of astaxanthin of more than 84%, and the loading amount can reach up to about 60%, so that more astaxanthin can be loaded with less carrier protein.

[0018] Preferably, in step S1, the carrier protein is at least one of bovine serum albumin, sodium caseinate, whey protein isolate, soy protein isolate, whey protein, pea protein, ovalbumin, whey protein concentrate, lysozyme or lactoferrin.

[0019] More preferably, in step S1, the carrier protein is at least one of bovine serum albumin, sodium caseinate, whey protein isolate or whey protein.

[0020] Further preferably, in step S1, the carrier protein is whey protein. The nano-astaxanthin aggregate complex prepared from whey protein has a higher encapsulation efficiency.

[0021] Preferably, in step S1, the step of adjusting the pH to 9-12 further includes a vortexing step.

[0022] More preferably, the vortexing time is 30 to 120 minutes and the rotation speed is 100 to 500 rpm.

[0023] Preferably, in step S2, the mixing further includes a vortexing step.

[0024] More preferably, the vortexing time is 30 to 120 minutes and the rotation speed is 100 to 500 rpm.

[0025] Preferably, in step S2, the concentration of the carrier protein in the composite solution is 0.0025-0.1 mg / mL.

[0026] More preferably, in step S2, the concentration of the carrier protein in the composite solution is 0.025-0.01 mg / mL. When the concentration of the carrier protein in the composite solution is within this range, the encapsulation efficiency of the nano-astaxanthin aggregate complex is higher.

[0027] Preferably, in step S2, the concentration of the carrier protein in the composite solution is 0.0025-0.025 mg / mL.

[0028] More preferably, in step S2, the concentration of the carrier protein in the composite solution is 0.0025-0.01 mg / mL.

[0029] Further preferably, in step S2, the concentration of the carrier protein in the composite solution is 0.0025-0.0030 mg / mL. When the concentration of the carrier protein in the composite solution is within this range, the loading amount of the nano-astaxanthin aggregate complex is higher, which is more cost-effective.

[0030] Preferably, in step S2, the volume ratio of the saturated ethanol solution of astaxanthin to the aqueous protein solution is 1:(4-9). Within this range, the astaxanthin in the nano-astaxanthin aggregate complex is astaxanthin H aggregate.

[0031] Preferably, in step S2, the volume ratio of the astaxanthin ethanol solution to the protein aqueous solution in the composite solution is 1:(1-3). In this range, the astaxanthin in the nano-astaxanthin aggregate complex is astaxanthin J aggregate.

[0032] Preferably, in step S3, the ethanol is removed by rotary evaporation.

[0033] More preferably, the vacuum degree of the rotary evaporation is 0.05-0.095 MPa, the temperature is 35-40° C., and the rotation speed is 50-150 rpm.

[0034] Preferably, in step S3, after the pH is adjusted to neutral, a step of adding water is further included.

[0035] More preferably, the volume of water added is equal to the volume of ethanol removed.

[0036] Preferably, the nano-astaxanthin aggregate complex exists in the form of an aqueous solution or a freeze-dried powder.

[0037] More preferably, the preparation process of the freeze-dried powder is: placing the aqueous solution of the nano-astaxanthin aggregate complex at -20 to -80°C for 24 to 48 hours, and then placing it under vacuum conditions at -70 to -32°C for 24 to 48 hours to obtain the freeze-dried powder.

[0038] A nano astaxanthin aggregate complex is prepared by the above preparation method.

[0039] The present invention also protects the use of the nano-astaxanthin aggregate complex in the preparation of food, medicine, cosmetics or feed.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The present invention uses pH to coordinate ethanol to induce carrier protein self-assembly, and embeds astaxanthin aggregates twice in a specific order of first removing ethanol and then adjusting pH, so that the prepared nano astaxanthin aggregate complex not only has good water solubility and storage stability, but also has excellent light stability and thermal stability, and high retention rate and bioavailability of astaxanthin after the digestion stage. In addition, the preparation method of the present invention has an encapsulation rate of astaxanthin of more than 84%, and the loading amount can reach up to about 60%, so that more astaxanthin can be loaded with less carrier protein. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is the UV-visible spectra of Examples 1 to 5.

[0043] Figure 2 It is the UV-visible spectra of Examples 4 and 6-8.

[0044] Figure 3 It is the UV-visible spectra of Examples 4 and 9-11.

[0045] Figure 4 It is the UV-visible spectra of Examples 2 and 12.

[0046] Figure 5 It is the UV-visible spectra of Examples 2 and 13-15.

[0047] Figure 6 It is the UV-visible spectra of Examples 4 and 16-18.

[0048] Figure 7 These are the color change graphs and UV-visible spectra of the nano-astaxanthin aggregate complex of Example 4 at different heat treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectra.

[0049] Figure 8The color change graph and UV-visible spectrum graph of the comparative nano-astaxanthin aggregate complex of Comparative Example 1 at different heat treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectrum graph.

[0050] Fig. 9 The color change graph and UV-visible spectrum graph of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 at different heat treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectrum graph.

[0051] Fig.10 These are the color change graphs and UV-visible spectra of the nano-astaxanthin aggregate complex of Example 4 at different light treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectra.

[0052] Fig.11 The color change graph and UV-visible spectrum graph of the comparative nano-astaxanthin aggregate complex of Comparative Example 1 at different light treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectrum graph.

[0053] Fig.12 The color change graph and UV-visible spectrum graph of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 at different light treatment times; Figure A is the color change graph, and Figure B is the UV-visible spectrum graph.

[0054] Fig.13 These are the color change graphs and UV-visible spectra of the nano-astaxanthin aggregate complex of Example 4 at different storage times; Figure A is the color change graph, and Figure B is the UV-visible spectra.

[0055] Fig.14 The freeze-dried powder image and the color image after reconstitution of the nano-astaxanthin aggregate complex of Example 4 and Example 2 are shown.

[0056] Fig.15 Astaxanthin retention rate graph and bioavailability graph of the nano-astaxanthin aggregate complex (J-AST-BSA) prepared in Example 4 and the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 at different in vitro digestion stages; wherein Figure A is a graph of astaxanthin aggregate retention rate at different in vitro digestion stages, and Figure B is a graph of bioavailability. DETAILED DESCRIPTION

[0057] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0058] The encapsulation efficiency and loading amount of astaxanthin were calculated as follows:

[0059] Take 0.2 mL of nano-astaxanthin aggregate complex in a centrifuge tube, add 1 mL of n-hexane, vortex for 1 min, and centrifuge at 10000 rpm for 10 min. Take the supernatant, blow nitrogen to remove the n-hexane, use 1 mL of DMSO to dissolve astaxanthin, measure the absorbance of the supernatant at 478 nm with an enzyme marker, calculate the astaxanthin concentration through the standard curve, and record it as unencapsulated astaxanthin.

[0060] Take 0.2mL of nano-astaxanthin aggregate complex in a centrifuge tube and mix it with 1.3mL of dichloromethane: methanol (v / v, 2:1) solution, vortex for 30s and centrifuge at 10000rpm for 10min, collect the organic layer, repeat the above steps until the water layer is colorless, use an enzyme marker to measure the absorbance of the organic layer at 478nm, calculate the concentration of astaxanthin by the standard curve, and record it as total astaxanthin. Calculate the encapsulation efficiency and loading amount of astaxanthin according to the following formula.

[0061]

[0062] Example 1

[0063] The present invention provides a method for preparing a nano-astaxanthin aggregate complex, comprising the following steps:

[0064] (1) At 25° C. in the dark, 0.0024 g of astaxanthin (AST) was dissolved in 40 mL of anhydrous ethanol, vortexed for 60 min, and centrifuged at 4000 rpm for 15 min to remove undissolved astaxanthin particles to obtain a saturated ethanol solution of astaxanthin.

[0065] (2) Dissolve bovine serum albumin (BSA) in water at room temperature and stir. Adjust the pH to 11.0 with 1 mol / L NaOH solution and vortex at 300 rpm for 90 min to obtain a protein aqueous solution.

[0066] (3) Mixing the saturated ethanol solution of astaxanthin from step (1) and the protein aqueous solution from step (2), vortexing for 120 min at a speed of 300 rpm to obtain a composite solution, wherein the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution is 1:9; and the concentration of the carrier protein in the composite solution is 0.025 mg / mL.

[0067] (4) removing the ethanol in the composite solution of step (3) by rotary evaporation, wherein the vacuum degree of the rotary evaporation is 0.09 MPa, the temperature is 35° C., and the rotation speed is 100 rpm; then adjusting the pH to 7.0 with 1 mol / L hydrochloric acid solution, and adding water with an equal volume to the evaporated ethanol to obtain a nano-astaxanthin aggregate complex.

[0068] Embodiments 2 to 5

[0069] Examples 2 to 5 provide a series of methods for preparing nano-astaxanthin aggregate complexes, which differ from Example 1 in the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution in step (3), as shown in Table 1. The concentration of the carrier protein in the composite solution obtained in step (3) of Examples 2 to 5 is 0.025 mg / mL, and the concentration of the carrier protein in the composite solution can be regulated by selecting a protein aqueous solution with different initial concentrations.

[0070] Table 1 Differences between Examples 1 to 5

[0071]

[0072] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 1 to 5 were subjected to UV-visible spectroscopy, and the parameters were set to a scanning range of 300 to 800 nm. The UV-visible spectra of Examples 1 to 5 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the astaxanthin monomer has an absorption peak at 478nm; the absorption peak of the nano-astaxanthin aggregate complex of Examples 1 to 2 is blue-shifted to 380-390nm, and astaxanthin exists in the form of H aggregate; the absorption peak of the nano-astaxanthin aggregate complex of Examples 3 to 5 is red-shifted to 517nm and is accompanied by a shoulder peak of 560nm, and astaxanthin exists in the form of J aggregate.

[0073] Embodiments 6 to 8

[0074] Examples 6 to 8 provide a series of methods for preparing nano-astaxanthin aggregate complexes, which differ from Example 4 in the concentration of the carrier protein in the composite solution obtained in step (3) (while maintaining the volume ratio of the saturated ethanol solution of astaxanthin and the protein aqueous solution at 4:6, the concentration of the carrier protein in the composite solution can be regulated by selecting protein aqueous solutions with different initial concentrations), as shown in Table 2.

[0075] Table 2 Differences between Example 4 and Examples 6 to 8

[0076]

[0077] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 4 and 6 to 8 were subjected to UV-visible spectroscopy measurement, and the parameters were set to a scanning range of 300 to 800 nm. The UV-visible spectra of Examples 4 and 6 to 8 are shown in FIG. Figure 2 As shown. Figure 2It can be seen that the absorption peak λmax of the nano-astaxanthin aggregate complex prepared in Examples 4 and 6 to 8 is 521 to 533 nm, accompanied by a shoulder peak of 550 to 575 nm, which indicates that when the carrier protein concentration of the composite solution is different, the preparation method of the present invention can prepare a nano-astaxanthin aggregate complex in which astaxanthin exists in the form of J aggregates.

[0078] The encapsulation efficiency and loading amount of the nano-astaxanthin aggregate complexes prepared in Examples 4 and 6-8 were measured. The results are shown in Table 3.

[0079] Table 3 Encapsulation efficiency and loading of nano-astaxanthin aggregate complexes prepared in Examples 4 and 6-8

[0080] Example 4 Example 6 Example 7 Example 8 Encapsulation rate / % 95.97±0.83 92.40±0.83 95.75±0.72 94.87±0.14 Load / % 10.54±0.37 61.93±0.21 16.19±0.51 2.41±0.11

[0081] As can be seen from Table 3, as the concentration of the carrier protein in the composite solution gradually increases, the encapsulation efficiency shows a trend of first increasing and then decreasing, and the maximum encapsulation efficiency is reached when the concentration of the carrier protein in the composite solution is 0.025 mg / mL. Under the conditions of different carrier protein concentrations in the composite solution, the preparation method of the nano-astaxanthin aggregate complex of the present invention can make the astaxanthin encapsulation efficiency above 90%, and up to 95.97%. As the concentration of the carrier protein in the composite solution gradually increases, the loading amount gradually decreases, and the preparation method of the nano-astaxanthin aggregate complex of the present invention can load more astaxanthin with less carrier protein.

[0082] Embodiments 9 to 11

[0083] Examples 9 to 11 provide a series of methods for preparing nano-astaxanthin aggregate complexes, which differ from Example 4 in the pH in step (2), as shown in Table 4.

[0084] Table 4 Differences between Example 4 and Examples 9 to 11

[0085] Example 4 Example 9 Example 10 Embodiment 11 pH 11 9 10 12

[0086] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 4 and 9 to 11 were subjected to UV-visible spectroscopy, and the parameters were set to a scanning range of 300 to 800 nm. The UV-visible spectra of Examples 4 and 9 to 11 are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the absorption peak λmax of the nano-astaxanthin aggregate complex prepared in Examples 4 and 9 to 11 is 521 to 533 nm, accompanied by a shoulder peak of 550 to 575 nm, which indicates that the preparation method of the present invention can successfully prepare a nano-astaxanthin aggregate complex under different pH conditions, and the astaxanthin in the nano-astaxanthin aggregate complex exists in the form of J aggregate.

[0087] The encapsulation efficiency of the nano-astaxanthin aggregate complexes prepared in Examples 4 and 9-11 was measured. The results are shown in Table 5.

[0088] Table 5 Encapsulation efficiency of nano-astaxanthin aggregate complexes prepared in Examples 4 and 9-11

[0089] Example 4 Example 9 Example 10 Embodiment 11 Encapsulation rate / % 95.97±0.83 93.49±0.79 92.87±0.21 89.51±0.22

[0090] As can be seen from Table 5, when the pH is 9 and pH is 10, the encapsulation efficiency is similar and there is no significant difference (p>0.05). When the pH increases to 11, the encapsulation efficiency increases significantly (p<0.05), but when the pH continues to increase to 12, the encapsulation efficiency decreases significantly (p<0.05). The reason is that under the alkaline condition, the bovine serum albumin is over-denatured and the structure is too loose, which affects the second encapsulation process, resulting in a decrease in the encapsulation efficiency.

[0091] Example 12

[0092] This embodiment provides a method for preparing a nano-astaxanthin aggregate complex, which is different from Example 2 in that the concentration of the carrier protein in the composite solution in step (3) is 0.0025 mg / mL.

[0093] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 2 and 12 were subjected to UV-visible spectroscopy, and the parameters were set to a scanning range of 300-800 nm. The UV-visible spectra of Examples 2 and 12 are shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the absorption peak λmax of the nano-astaxanthin aggregate complex prepared in Examples 2 and 12 is 375-390 nm, which indicates that when the carrier protein concentration of the composite solution is different, the preparation method of the present invention can prepare a nano-astaxanthin aggregate complex in which astaxanthin exists in the form of H aggregate.

[0094] The encapsulation efficiency and loading capacity of the nano-astaxanthin aggregate complexes prepared in Examples 2 and 12 were measured. The results are shown in Table 6.

[0095] Table 6 Encapsulation efficiency and loading amount of nano-astaxanthin aggregate complexes prepared in Examples 2 and 12

[0096] Example 2 Example 12 Encapsulation rate / % 84.66±0.49 84.53±0.77 Load / % 3.18±0.12 11.32±0.08

[0097] It can be seen from Table 6 that when astaxanthin is in the form of H aggregate, the encapsulation efficiency of Example 2 (the concentration of the carrier protein in the composite solution is 0.025 mg / mL) is higher than the encapsulation efficiency of Example 12 (the concentration of the carrier protein in the composite solution is 0.0025 mg / mL), which is consistent with the case where astaxanthin is in the form of J aggregate (Examples 4 and 6).

[0098] Embodiments 13 to 15

[0099] Examples 13 to 15 provide a series of methods for preparing nano-astaxanthin aggregate complexes, which differ from Example 2 in the pH in step (2), as shown in Table 7.

[0100] Table 7 Differences between Example 2 and Examples 13 to 15

[0101] Example 2 Example 13 Embodiment 14 Embodiment 14 pH 11 9 10 12

[0102] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 2 and 13 to 15 were subjected to UV-visible spectroscopy measurement, and the parameters were set to a scanning range of 300 to 800 nm. The UV-visible spectra of Examples 2 and 13 to 15 are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the absorption peak λmax of the nano-astaxanthin aggregate complex prepared in Examples 2 and 13 to 15 is 375 to 390 nm, which indicates that the preparation method of the present invention can successfully prepare the nano-astaxanthin aggregate complex in the form of H aggregate under different pH conditions.

[0103] Embodiments 16 to 18

[0104] Examples 16 to 18 provide a series of methods for preparing nano-astaxanthin aggregate complexes, which differ from Example 4 in the carrier protein in step (2), as shown in Table 8.

[0105] Table 8 Differences between Example 4 and Examples 16 to 18

[0106]

[0107] The nano-astaxanthin aggregate complex and astaxanthin monomer (AST) prepared in Examples 4 and 16 to 18 were subjected to UV-visible spectroscopy measurement, and the parameters were set to a scanning range of 300 to 800 nm. The UV-visible spectra of Examples 4 and 16 to 18 are shown in FIG. Figure 6 As shown. Figure 6 It can be seen that the absorption peak λmax of the nano-astaxanthin aggregate complex prepared in Examples 4 and 16-18 is 521-533 nm, accompanied by a shoulder peak of 550-575 nm, which indicates that the nano-astaxanthin aggregate complex can be successfully prepared by using common carrier proteins.

[0108] The encapsulation efficiency of the nano-astaxanthin aggregate complexes prepared in Examples 4 and 16 to 18 was measured. The results are shown in Table 9.

[0109] Table 9 Encapsulation efficiency of nano-astaxanthin aggregate complexes prepared in Examples 4 and 16-18

[0110] Example 4 Example 16 Embodiment 17 Embodiment 18 Encapsulation rate / % 95.97±0.83 92.55±0.16 93.06±0.22 97.77±0.42

[0111] It can be seen from Table 9 that under the conditions of different carrier proteins, the preparation method of the nano-astaxanthin aggregate complex of the present invention can make the astaxanthin encapsulation rate above 90%, and the highest can reach 97.77%.

[0112] Comparative Example 1

[0113] This comparative example provides a method for preparing a comparative nano-astaxanthin aggregate complex, which is different from Example 4 in that the pH in step (2) is 7.0.

[0114] The encapsulation efficiency of the nano-astaxanthin aggregate complex prepared in Example 4 and the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 was measured, and the results are shown in Table 10.

[0115] Table 10 Encapsulation efficiency of Example 4 and Comparative Example 1

[0116] Example 4 Comparative Example 1 Encapsulation rate / % 95.97±0.83 86.96%±0.16%

[0117] It can be seen from Table 10 that since the specific pH was not adjusted to expose the internal hydrophobic groups of the carrier protein, the astaxanthin aggregates were only embedded once, and the encapsulation efficiency of the comparative nano-astaxanthin aggregate complex was very low.

[0118] Comparative Example 2

[0119] This comparative example provides a method for preparing a comparative nano-astaxanthin aggregate complex, which is different from Example 4 in that: in step (4), rotary evaporation is not performed, that is, ethanol is not removed.

[0120] Comparative Examples 3 to 6

[0121] The difference between Comparative Examples 3 to 6 and Example 1 is the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution in step (3), as shown in Table 11. Among them, the concentration of the carrier protein in the composite solution obtained in step (3) of Comparative Examples 3 to 6 is 0.025 mg / mL, and the concentration of the carrier protein in the composite solution can be regulated by selecting a protein aqueous solution with different initial concentrations.

[0122] Table 11 Differences between Comparative Examples 3 to 6

[0123]

[0124] The astaxanthin in the complexes prepared in Comparative Examples 3 to 6 exists in the form of monomers rather than aggregates, that is, complexes of astaxanthin aggregates cannot be successfully obtained.

[0125] Performance Testing

[0126] (1) Thermal stability: 10 mL of the nano-astaxanthin aggregate complex of Example 4 and the comparative nano-astaxanthin aggregate complex of Comparative Examples 1-2 were placed in an amber glass bottle and heat treated at 60°C for 4 h. The color change of the solution was observed and the particle size of the solution was measured at 0 h, 0.5 h, 1 h, 2 h and 4 h, respectively. The UV-visible spectrum was measured with an ELISA instrument to observe the position and intensity changes of the absorption peaks, thereby judging the thermal stability of the nano-astaxanthin aggregate complex. The particle size results are shown in Table 12.

[0127] Table 12 Particle size results of nano-astaxanthin aggregate complexes in thermal stability experiments

[0128]

[0129]

[0130] Figures 7 to 9 The color change diagrams and UV-visible spectra of the nano-astaxanthin aggregate complex of Example 4 and the comparative nano-astaxanthin aggregate complex of Comparative Examples 1-2 at different heat treatment times are shown respectively; Figures 7 to 9 A is the color change diagram, Figures 7 to 9 B is the UV-visible spectrum.

[0131] As can be seen from Table 12, the particle size of the nano-astaxanthin aggregate complex of Example 4 changes slightly at different heat treatment times, and the particle size distribution is uniform. Figure 7 It can be seen that the color of the nano-astaxanthin aggregate complex of Example 4 changes little at different heat treatment times, and the change in the absorbance peak after heat treatment is small. It can be seen that the nano-astaxanthin aggregate complex prepared by the present invention has good thermal stability.

[0132] As can be seen from Table 12, the comparative nano-astaxanthin aggregate complex of Comparative Example 1 is difficult to completely dissociate the inherent large-sized carrier protein particles in the protein aqueous solution because the carrier protein is only treated with ethanol, so the particle size is larger than that of Example 4, and the particle size distribution is uneven; as the heat treatment time increases, the carrier protein particles are prone to unfolding and reorganization, resulting in a significant change in particle size, indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 has poor thermal stability. Figure 8 It can be seen that the absorbance peak value of the comparative nano-astaxanthin aggregate complex of Comparative Example 1 changes greatly after heat treatment, further indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 has poor thermal stability.

[0133] It can be seen from Table 12 that the particle size of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 is larger than that of Example 4. The reason is that: Step S4 does not remove the ethanol, which interferes with the folding process of the carrier protein particles. The carrier protein cannot undergo a complete "dissociation-unfolding-folding" cycle, and its structure may remain in an incompletely folded or abnormally folded state, resulting in the internal structure of the carrier protein particles being too loose. In addition, carrier protein particles in an incompletely folded or abnormally folded state will aggregate or dissociate under the influence of heat treatment, resulting in a phenomenon in which the particle size fluctuates with the heat treatment time. The above results in the poor thermal stability of the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 2. Fig. 9 It can be seen that the absorbance peak value of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 changes greatly after heat treatment, further indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 2 has poor thermal stability.

[0134] (2) Light stability: 10 mL of the nano-astaxanthin aggregate complex of Example 4 and the comparative nano-astaxanthin aggregate complex of Comparative Examples 1-2 were placed in a transparent glass bottle and irradiated under a 30W incandescent lamp for 24 h, with the distance from the bulb to the static liquid surface being 25 cm. Samples were taken at 0 h, 1 h, 2 h, 4 h, 8 h, and 24 h, respectively, and the color change of the solution was observed, the particle size of the solution was measured, and the ultraviolet-visible spectrum was measured with an ELISA instrument to observe the position and intensity change of the absorption peak, thereby judging the light stability of the nano-astaxanthin aggregate complex. The results of the particle size are shown in Table 13.

[0135] Table 13 Particle size results of nano-astaxanthin aggregate complexes in photostability experiments

[0136]

[0137] Figures 10-12 The color change diagrams and UV-visible spectra of the nano-astaxanthin aggregate complex of Example 4 and the comparative nano-astaxanthin aggregate complex of Comparative Examples 1-2 at different light treatment times are shown respectively; Figures 10-12 Figure A is a color change diagram. Figures 10-12 Figure B is the UV-visible spectrum.

[0138] It can be seen from Table 13 that the particle size of the nano-astaxanthin aggregate complex of Example 4 changes little under different light treatment times, and the overall distribution of the particle size is relatively uniform; Fig.10 It can be seen that the color of the nano-astaxanthin aggregate complex of Example 4 changes little under different light treatment times, and the change of the absorbance peak after light irradiation is small. Therefore, it can be seen that the nano-astaxanthin aggregate complex prepared by the present invention has good light stability.

[0139] As can be seen from Table 13, the comparative nano-astaxanthin aggregate complex of Comparative Example 1 is difficult to completely dissociate the inherent large-sized carrier protein particles in the protein aqueous solution because the carrier protein is only treated with ethanol, so the particle size is larger than that of Example 4, and the particle size distribution is uneven; as the light treatment time increases, the carrier protein particles are prone to unfolding and reorganization, resulting in a significant change in particle size, indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 has poor light stability. Fig.11 It can be seen that the peak value of the absorbance of the comparative nano-astaxanthin aggregate complex of Comparative Example 1 changes greatly after light treatment, further indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 1 has poor photostability.

[0140] It can be seen from Table 13 that the particle size of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 is larger than that of Example 4. The reason is that: Step S4 does not remove the ethanol, which interferes with the folding process of the carrier protein particles. The carrier protein cannot undergo a complete "dissociation-unfolding-folding" cycle, and its structure may remain in an incompletely folded or abnormally folded state, resulting in the internal structure of the carrier protein particles being too loose. In addition, carrier protein particles in an incompletely folded or abnormally folded state will aggregate or dissociate under the influence of light treatment, resulting in a phenomenon in which the particle size fluctuates with the light treatment time. The above results in the poor photostability of the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 2. Fig.12 It can be seen that the peak value of the absorbance of the comparative nano-astaxanthin aggregate complex of Comparative Example 2 changes greatly after light treatment, further indicating that the comparative nano-astaxanthin aggregate complex prepared in Comparative Example 2 has poor photostability.

[0141] (3) Storage stability: 10 mL of the nano-astaxanthin aggregate complex of Example 4 was placed in an amber glass bottle and dark-treated in a 25°C thermostat for 28 days. The particle size of the nano-astaxanthin aggregate complex was measured at 0 days, 7 days, 14 days, 21 days, and 28 days, and the color change was observed. The UV-visible spectrum was measured with an ELISA instrument to observe the position and intensity changes of the absorption peaks, thereby determining the storage stability of the nano-astaxanthin aggregate complex. The results of the particle size are shown in Table 14.

[0142] Table 14 Particle size results of nano-astaxanthin aggregate complexes in storage stability experiments

[0143]

[0144] As can be seen from Table 14, the particle size of the nano-astaxanthin aggregate complex of Example 4 changes little at different storage times, and the particle size distribution is uniform. Fig.13 The color change diagram and UV-visible spectrum diagram of the nano-astaxanthin aggregate complex of Example 4 at different storage times; Figure A is the color change diagram, and Figure B is the UV-visible spectrum diagram. Fig.13 It can be seen that the color of the nano-astaxanthin aggregate complex of Example 4 changes little at different storage times, and the peak value of the nano-astaxanthin aggregate complex changes little, which indicates that the nano-astaxanthin aggregate complex prepared by the present invention undergoes less degradation under long-term storage and has good storage stability.

[0145] (4) Determination of the resolubility properties of freeze-dried powder of nano-astaxanthin aggregate complex

[0146] The nano-astaxanthin aggregate complex of Example 2 and Example 4 is placed in a 50 mL centrifuge tube, covered with plastic wrap, and pierced with small holes for ventilation. The pre-freeze-drying process is to place it in a -80°C refrigerator for 24 hours. Use a vacuum freeze dryer to freeze-dry and sublimate to remove moisture. The freeze-drying process is to freeze-dry at -32°C for 48 hours to obtain the freeze-dried powder of the nano-astaxanthin aggregate complex, which is sealed, protected from light, and stored at -20°C for later use. The astaxanthin of the nano-astaxanthin aggregate complex obtained in Example 4 exists in the form of J aggregates, and its freeze-dried powder is light purple-pink; the astaxanthin of the nano-astaxanthin aggregate complex obtained in Example 2 exists in the form of H aggregates, and its freeze-dried powder is yellow-orange. The freeze-dried powder of the nano-astaxanthin aggregate complex is re-dissolved with ultrapure water, and the color of the nano-astaxanthin aggregate complex after redissolution is observed, such as Fig.14 As shown. Fig.14 It can be seen that the color of the freeze-dried powder of the nano-astaxanthin aggregate complex does not change before and after re-dissolution, and the solution is clear and transparent after re-dissolution, indicating that the freeze-dried powder of the nano-astaxanthin aggregate complex prepared by the present invention has good water solubility.

[0147] The particle size, PDI and potential of the reconstituted solution of the freeze-dried powder of the nano-astaxanthin aggregate complex were measured within 1 hour after reconstitution, and compared with the particle size, PDI and potential before making the freeze-dried powder. The change value Δ was calculated according to the following formula, see Table 15.

[0148] Δ = nano-astaxanthin aggregate complex after re-dissolution - nano-astaxanthin aggregate complex before freeze-dried powder;

[0149] Table 15 Determination of the reconstitution properties of the freeze-dried powder of nano-astaxanthin aggregate complex

[0150] ΔParticle size / nm Δ potential / mv ΔPDI Example 2 20.66±57.22 -15.07±0.75 0.05±0.05 Example 4 18.77±7.44 -5.00±0.26 0.04±0.02

[0151] As can be seen from Table 15, the changes in particle size, PDI and potential of the freeze-dried powder of the nano-astaxanthin aggregate complex prepared in Example 2 and Example 4 after re-dissolution are small, indicating that the freeze-dried powder of the nano-astaxanthin aggregate complex prepared in the present invention is dispersed in water in a stable state after re-dissolution, and can achieve the effect before freeze-drying. Therefore, the nano-astaxanthin aggregate complex can also be stored in a more convenient way of freeze-dried powder or used as an additive for food, medicine, cosmetics or feed without affecting its properties after re-dissolution, and has a wide range of application prospects.

[0152] (5) Static in vitro simulated digestion

[0153] Refer to the INFOGEST standard static in vitro simulated digestion method, the specific steps are as follows:

[0154] Simulated oral digestion stage: 15 mg mucin was dissolved in 4 mL SSF and stirred overnight at 4 ° C. Accurately weigh 5 mL of the nano-astaxanthin aggregate complex sample prepared in Example 4 and Comparative Example 1 and mix them evenly with 4 mL SSF (containing mucin), α-amylase (0.6 g / L), and 25 μL 0.3 mol / LCaCl2 solution, adjust the pH to pH = 7.0 with hydrochloric acid, and add distilled water to the entire digestion system to 10 mL. The mixed sample oral digestion liquid was placed in a constant temperature shaker at 37 ° C and 150 r / min for 2 minutes to obtain an oral digestion sample.

[0155] Simulated gastric digestion stage: 10 mL of the oral digested sample was mixed evenly with 8 mL SGF and 5 μL 0.3 mol / LCaCl2 solution, and pepsin (800 U / mg) was added to make its activity reach 2000 U / mL in the final gastric digestion mixture. The pH was reduced to pH=3.0 with hydrochloric acid, and the whole digestion system was supplemented to 20 mL with distilled water. The mixed sample gastric digestion liquid was placed in a constant temperature shaker at 37°C and 150 r / min for 2 hours to obtain a gastric digestion sample.

[0156] Simulated small intestinal digestion stage: 20 mL of the sample after the gastric digestion stage was completed was mixed with 8 mL SIF, 5 mL lipase (438 U / mg) and pancreatin (4.5 U / mg), 3 mL bile salt (finally reaching 10 mM in the digestion mixture), and 40 μL 0.3 mol / LCaCl2 solution. The pH was adjusted to pH = 7.0 with sodium hydroxide, and the whole digestion liquid was supplemented with distilled water to 40 mL. The mixed sample intestinal digestion liquid was placed in a constant temperature shaker at 37 ° C and 150 r / min for 2 hours of shaking digestion, and titrated with 0.25 M sodium hydroxide solution to maintain a neutral environment (pH = 7.0) for the whole system. The content of astaxanthin aggregates C was measured during the simulation of oral digestion (2 minutes of the whole static in vitro simulated digestion process), gastric digestion (32 minutes, 62 minutes and 122 minutes of the whole static in vitro simulated digestion process) and small intestinal digestion (152 minutes, 182 minutes and 242 minutes of the whole static in vitro simulated digestion process) t The astaxanthin aggregate content in the sample before static in vitro simulated digestion was taken as the initial astaxanthin aggregate content C0, and the retention rate was calculated according to the following formula. The results are shown in Fig.15 As shown in Figure A:

[0157]

[0158] The astaxanthin aggregates in the digestive fluid after the small intestinal digestion are divided into two parts. One part is the astaxanthin aggregates that have not been degraded but may still be wrapped in the carrier protein. This part of astaxanthin cannot be absorbed and utilized by the intestine; the other part is the undegraded astaxanthin aggregates released from the carrier protein. This part of astaxanthin aggregates can be absorbed and utilized by the intestine. The end point of the simulated small intestinal digestion is the end point. Take 6mL of the sample at the end point of the digestion and centrifuge (10000rpm, 30min) to determine the content of astaxanthin aggregates in the supernatant. The astaxanthin content in the sample before the static in vitro simulated digestion is taken as the initial astaxanthin aggregate content. The bioavailability is calculated according to the following formula. The results are as follows Fig.15 As shown in Figure B:

[0159]

[0160] from Fig.15As can be seen from Figure A, after the oral digestion stage, the astaxanthin aggregate retention rates of Example 4 and Comparative Example 1 are not much different; after the end of gastric digestion (122 minutes), the astaxanthin aggregate retention rate of Example 4 is 94.81%, while the astaxanthin aggregate retention rate of Comparative Example 1 is 89.30%, which indicates that during the gastric digestion stage, the astaxanthin aggregates in the nano-astaxanthin aggregate complex prepared by the present invention can be well encapsulated and protected, thereby reducing degradation during gastric digestion; after the end of small intestinal digestion (242 minutes), the astaxanthin aggregate retention rate of Example 4 is 87.20%, while the astaxanthin aggregate retention rate of Comparative Example 1 is significantly reduced to 56.83%, further indicating that the nano-astaxanthin aggregate complex prepared by the present invention can ensure that most of the astaxanthin aggregates are stably present and not degraded during the digestion process. Fig.15 As shown in Figure B, the bioavailability of the nano-astaxanthin aggregate complex prepared in Comparative Example 1 is 15.76%, while the bioavailability of the nano-astaxanthin aggregate complex prepared in Example 4 is as high as 40.97%, which indicates that the nano-astaxanthin aggregate complex prepared in the present invention can still stably exist without being degraded and can be absorbed by the intestine after being digested in the mouth, stomach and small intestine, thereby making the bioavailability high.

[0161] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a nano-astaxanthin aggregate complex, characterized in that: The following steps are involved: S1. The carrier protein is dissolved in water and the pH is adjusted to 9-12 to obtain a protein aqueous solution; S2. The protein aqueous solution and the saturated ethanol solution of astaxanthin are mixed to obtain a composite solution; S3. first removing the ethanol in the composite solution, and then adjusting the pH to neutral to obtain the nano-astaxanthin aggregate complex; In step S2, the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution is 1:(1-9); the concentration of the carrier protein in the composite solution is 0.002-0.12 mg / mL.

2. The preparation method according to claim 1, characterized in that: In step S1, the carrier protein is at least one of bovine serum albumin, sodium caseinate, whey protein isolate, soy protein isolate, whey protein, pea protein, ovalbumin, whey protein concentrate, lysozyme or lactoferrin.

3. The preparation method according to claim 1, characterized in that: In step S2, the mixing further includes a vortexing step.

4. The preparation method according to claim 1, characterized in that: In step S2, the concentration of the carrier protein in the composite solution is 0.0025-0.1 mg / mL.

5. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution is 1:(4-9).

6. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of the saturated ethanol solution of astaxanthin to the protein aqueous solution is 1:(1-3).

7. The preparation method according to claim 1, characterized in that: In step S3, the ethanol is removed by rotary evaporation.

8. The use according to claim 1, characterized in that The nano-astaxanthin aggregate complex exists in the form of aqueous solution or freeze-dried powder.

9. A nano-astaxanthin aggregate complex, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nano-astaxanthin aggregate complex according to claim 9 in the preparation of food, medicine, cosmetics or feed.

Citation Information

Patent Citations

  • Anti-oxidative stress nano reagent as well as preparation method and application thereof

    CN113599369A

  • Food-grade carotenoid nanocapsule product and preparation method thereof

    CN114431467A

  • Method for inducing protein to assemble nano-embedded xanthophyll through cooperation of pH and ethanol, protein-based xanthophyll nano-particles and application of protein-based xanthophyll nano-particles

    CN116391864A

  • Oil-free carotenoid composition

    US20200000736A1

Cited By

  • Sample pad for urine beta amyloid protein detection, test strip containing sample pad and application of test strip

    CN121208364A

  • Astaxanthin binding protein from Antarctic krill and application of astaxanthin binding protein

    CN121824719A

  • Astaxanthin binding protein derived from euphausia superba and use thereof

    CN121824719B